Effect of nacl salinity on seed germination and seedling emergence of purple passion fruit (passiflora edulis sims) (2014)
The purple passion fruit is propagated by seeds, but factors, such as hardiness and impermeability of the testa and salinity and pH of the soil, give rise to problems in germination and uniformity of seedlings. The objectives of the study were to evaluate the effect of different NaCl concentrations (0, 30, 60, 90, and 120 mM, corresponding to 0.8, 3.0, 6.0, 9.0, and 12.2 dS m-1) on the germination and emergence of purple passion fruit seeds. For the germination test, 50 seeds per Petri dish were used, which were watered with a saline solution weekly. A seed was considered germinated when the radicle reached 2 mm. In the case of seedling emergence, 50 seeds were sown in cleaned river sand at a 1 cm depth on polystyrene trays, covered with transparent plastic film. They were irrigated weekly with different NaCl concentrations and the electrical conductivity (EC) of the substrate was measured. A seedling was considered emerged when the hypocotyl was fully erect. The results  howed significant differences, with germination being higher in seeds treated with 30 mM NaCl than in the control seeds, and no statistical differences for the 60 and 90 mM NaCl treatments. The emergence was significantly higher in the 0 (0.05 dS m-1  of the substrate) and 30 mM NaCl (0.71 dS m-1) treated seeds when compared with 60 mM (1.25 dS m-1), 90 mM (1.69 dS m-1) and 120 mM NaCl (2.30 dS m-1 of the substrate). There was a decline in the chlorophyll contents of the seedling cotyledons and an increased substrate EC with increasing NaCl concentrations.